WORKLOAD, WORK STRESS AND WORK MOTIVATION ON TURNOVER INTENTION OF EMPLOYEES CV. BRILLIANO PERKASA GROUP IN SURABAYA - Bayu Rama Laksono; Widiar Onny Kurniawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Human resources are an important component in efforts to achieve company targets through the resulting performance. Every company that wants maximum work results from its human resources, the company must provide workers' rights and facilitate workers with facilities that must be available in a company. With the attention given by the company to workers, it will have a good impact on the company's working relationship with the workers or employees of the company. Employees have a big impact on companies that want to achieve their targets quickly, contributing to the company must be maximal. The approach used to find the method quantitatively, with a population of all employees of CV. Brilliano Perkasa Group as many as 40 employees & 40 respondents were selected as samples. The findings from the results of the tests conducted by the author show that partially and simultaneously there is an effect of workload, work stress and work motivation on turnover intention.